Tuturan Melarang dalam Komik Yotsubato Karya Kiyohiko Azuma - Yasa, I Komang Triadi Merta; Andry Anita Dewi, Ni Made; Yuliani Giri, Ni Luh Kade (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 2 No 1 (2020)DO - 10.24843/JS.2020.v02.i01.p02, 2020)
The research entitled “Speech Acts of Prohibition in Comic Yotsubato by Kiyohiko Azuma” is aimed to identify various form of speech acts of prohibition and the factors behind the use of the said speech acts in the comic Yotsubato by Kiyohiko Azuma. This research applied the theory of speech acts by Wijana (1996) and level of politeness factors according to Mizutani and Mizutani (1987). The method of collecting data used in the research is attentive observation method, which is done by observing the speech in the comic. Afterwards, the obtained data is noted by applying note-taking technique. The data analysis is done by using pragmatic identity method. Later on, in the data presentation, informal method is used. The result of the analysis indicates that in the comic Yotsubato, found 9 data that categorized as direct speech acts of prohibition and 7 data that categorized as indirect speech acts of prohibition. Then, there are 4 factors behind the use of the speech acts of prohibition in the comic Yatsubato, namely 1) familiarity factors ; 2) age ; 3) social distance; and 4) gender.